Banks, Payments, and Coordination - McAndrews, James J.; Roberds, William (Journal of Financial Intermediation, 1995)
Banks are modeled as Bryant/Diamond-Dybvig "insurers" against the risk of early consumption. Consumption claims must be verified by clearing and settlement. A clearinghouse does this efficiently as long as banks are sufficiently liquid. If liquidity requirements cannot be enforced against all banks then the threat of panics is necessary to induce banks to hold sufficient liquidity. If the clearinghouse can issue emergency currency, then banks can coexist with less liquid institutions. However, if banks′ return to holding reserves is low during "normal times," then there must be times when the return to liquidity is abnormally high. We associate these episodes with the panics of the National Banking Era. Journal of Economic Literature Classification Numbers: 042, 311, 314.